2004
DOI: 10.1590/s1517-83822004000300005
|View full text |Cite
|
Sign up to set email alerts
|

Survival of endophytic diazotrophic bacteria in soil under different moisture levels

Abstract: The effects of soil moisture on the survival of three diazotrophic bacteria species (Azospirillum amazonense, Gluconacetobacter diazotrophicus and Azospirillum brasilense) were tested. Soil moisture had little influence on the survival of A. brasilense, which is considered a free-living species. On the other hand, increased soil moisture extended the survival of the endophytes A. amazonense and G. diazotrophicus. These results indicate that nitrogen-fixing endophytic species are more affected by soil moisture … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 29 publications
(11 citation statements)
references
References 21 publications
(21 reference statements)
0
11
0
Order By: Relevance
“…Thermal treatment of sugarcane setts (30 minutes at 52 • C), applied to eliminate phytopathogenic bacteria responsible for the ratoon stanting disease, did not eliminate the endophyte , confirming that the setts are one way of dissemination of the bacteria. In addition, it has been observed that the bacteria have a very low rate of survival in soil (Baldani et al 1997a), although it has been demonstrated that the rate of cell death depends on the humidity at the time of inoculation into the soil (Oliveira et al 2004). It is already known that the bacterial population is also influenced by the nutritional stage of the sugarcane plants (Reis-Jr et al 2000) and that nitrogen fertilization also decreases the population of G. diazotrophicus associated with the sugarcane (Fuentes-Ramírez et al 1999).…”
Section: Plant Dependencementioning
confidence: 99%
“…Thermal treatment of sugarcane setts (30 minutes at 52 • C), applied to eliminate phytopathogenic bacteria responsible for the ratoon stanting disease, did not eliminate the endophyte , confirming that the setts are one way of dissemination of the bacteria. In addition, it has been observed that the bacteria have a very low rate of survival in soil (Baldani et al 1997a), although it has been demonstrated that the rate of cell death depends on the humidity at the time of inoculation into the soil (Oliveira et al 2004). It is already known that the bacterial population is also influenced by the nutritional stage of the sugarcane plants (Reis-Jr et al 2000) and that nitrogen fertilization also decreases the population of G. diazotrophicus associated with the sugarcane (Fuentes-Ramírez et al 1999).…”
Section: Plant Dependencementioning
confidence: 99%
“…Decreased soil moisture or increased soil pH loosens bacterial attachment to the soil particles surfaces. Under adequate soil moisture and in the absence of the host plant, different PGPR species are adsorbed loosely on the surfaces of soil particles and hence can move to the roots of other plants (Oliveira et al 2004). …”
Section: Introductionmentioning
confidence: 99%
“…The amount of moisture present in soil at a particular time mostly depends on soil type. Plant wilting can be caused either by the plant or by the soil [18, 20] Soils having more water-holding capacity are more favorable for bacterial development and increase in soil moisture extended the survival of the endophytic bacteria [18]. Consistent with this notion, less disease severity was recorded for sandy loam soil as water holding capacity of sandy loam soil is less that silt loam and loam soil.…”
Section: Discussionmentioning
confidence: 97%